Knowledge, Attitudes, and Practice of Nursing Students about Insulin Therapy: A Cross-Sectional Study: Pengetahuan, Sikap, dan Praktik Mahasiswa Keperawatan tentang Terapi Insulin: Sebuah Studi Cross-Sectional - Husham Hussain Abdul-Ra’aoof; Ali Malik Tiryag; Maher Abdulameer Atiyah (Academia Open, 2024)
This study aims to assess the knowledge, attitudes, and practices of nursing students regarding insulin therapy. Conducted at the College of Nursing - University of Basrah, the research utilized a questionnaire to gather data from 200 participants over a six-month period. Results indicate a good overall level of knowledge about insulin therapy, a fair attitude towards it, and a medium level of suggested practice. Interestingly, while there was a significant correlation between participants' knowledge and gender, no discernible relationships were found between knowledge and other demographic variables, nor between attitudes and any demographic factors. This suggests the need for targeted educational interventions to improve attitudes and practices towards insulin therapy among nursing students. Highlights: Varied knowledge levels among nursing students. Positive attitudes towards insulin therapy. Need for tailored educational interventions. Keywords: Knowledge, Attitudes, Practice, Nursing Students, Insulin Therapy